Clinical pitfall with Chievitz's organ: A case report of tongue cancer patient. Issue 3 (May 2021) - Kimizuka, Sachiko; Fujihara, Hisako; Ito, Yumi; Takeda, Akira; Yamada, Hiroyuki; Hamada, Yoshiki
Abstract: Chievitz's organ, or the so-called juxtaoral organ of Chievitz's, is one of the normal structures located in the deep soft tissue around the medial pterygoid muscle at the height of the piercing mandible line. Although it has been first reported more than a century ago, its function remains unclear. Moreover, there were some reports stating that Chievitz's organ could be a clinical pitfall due to the similarity of its pathological feature to that of squamous cell carcinoma (SCC). In this report, we describe a case of tongue carcinoma in a 59-year-old man, whose determination of margin free line was quite challenging due to the existence of Chievitz's organ, which could narrowly avoid unnecessary additional resection. This patient received hemiglossectomy with neck dissection and immediate reconstruction using a radial forearm flap based on the result of imaging data and biopsy. Although intraoperative rapid diagnoses around the surgical margin were all negative, epithelial cell nests composed of small heterotopic cells were found in the permanent specimen from another slice of the same specimen. Fortunately, we achieved the final diagnosis of Chievitz's organ in a timely manner through a detailed pathological examination using serial sections of the area between the tumor edges together with these findings, which was quite tough. If it was found during surgical treatment, there was quite a possibility that additional unnecessary resection would have been performed. This case demonstrates the importance of the knowledge on Chievitz's organ for not only clinicians but also pathologists.